Eosinophils control the resolution of inflammation and draining lymph node hypertrophy through the proresolving mediators and CXCL13 pathway in mice. Issue 9 (2nd June 2014) - Tani, Yukako; Isobe, Yosuke; Imoto, Yuki; Segi‐Nishida, Eri; Sugimoto, Yukihiko; Arai, Hiroyuki; Arita, Makoto
Abstract : Resolution of inflammation is critical to restoration of tissue function after an inflammatory response. We previously demonstrated that 12/15‐lipoxygenase (12/15‐LOX)‐expressing eosinophils contribute to this process in murine zymosan‐induced peritonitis. In this study, eosinophils promoted resolution by regulating expression of macrophage CXCL13. Microarray analysis revealed that eosinophils significantly increased (~ 3‐fold) the expression of macrophage CXCL13 by a 12/15‐LOX‐dependent mechanism. CXCL13 depletion caused a resolution defect, with the reduced appearance of phagocytes carrying engulfed zymosan in the draining lymph nodes. Inflamed lymph node hypertrophy, a critical feature of the resolution process, was reduced by ~60% in eosinophil‐deficient mice, and adoptive transfer of eosinophils or administration of CXCL13 corrected this defect. Administration of the 12/15‐LOX‐derived mediator lipoxin A4 (LXA4 ) increased the expression of CXCL13 and restored the defect of lymph node hypertrophy in eosinophil‐deficient mice. These results demonstrate that eosinophils control the resolution of inflammation and draining lymph node hypertrophy through proresolving lipid mediators and the CXCL13 pathway in mice.—Tani, Y., Isobe, Y., Imoto, Y., Segi‐Nishida, E., Sugimoto, Y., Arai, H., Arita, M. Eosinophils control the resolution of inflammation and draining lymph node hypertrophy through the proresolving mediators and CXCL13 pathway in mice. FASEB J. 28, 4036‐4043 (2014). www.fasebj.org